2013
DOI: 10.1002/jbm.a.34940
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages behavior on different NIPAm‐based thermoresponsive substrates

Abstract: Thermoresponsive materials and surfaces are widely used in cell culture applications. There is a lot of research work employing thermoresponsive materials with various structure and compositions. However, little is known about the immunological response to the thermoresponsive materials. Macrophage‐like transformed murine cell line RAW264.7 was selected as it is a widely used standard model for immune activation analysis. This study proposes to compare the effects of thermoresponsive films with various composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…Previous work by Nash et al reported that cell growth on spin coated ultrathin poly(NIPAm‐co‐AcBzPh) films is similar to cell growth on TCP and thermanox positive controls and the results reported here support this finding . Numerous studies have demonstrated that cell growth is better on hydrophobic NIPAm based polymers such as poly(NIPAm‐co‐NtBAm) and therefore it stands to reason that cell growth would also be enhanced on poly(NIPAm‐co‐NtBAm‐co‐AcBzPh) compared to poly(NIPAm‐co‐AcBzPh) . This was not found to be the case as can be seen from Figure .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Previous work by Nash et al reported that cell growth on spin coated ultrathin poly(NIPAm‐co‐AcBzPh) films is similar to cell growth on TCP and thermanox positive controls and the results reported here support this finding . Numerous studies have demonstrated that cell growth is better on hydrophobic NIPAm based polymers such as poly(NIPAm‐co‐NtBAm) and therefore it stands to reason that cell growth would also be enhanced on poly(NIPAm‐co‐NtBAm‐co‐AcBzPh) compared to poly(NIPAm‐co‐AcBzPh) . This was not found to be the case as can be seen from Figure .…”
Section: Resultssupporting
confidence: 84%
“…The advancing contact angle profiles observed for the physically adsorbed thermoresponsive films indicate stick and slip type behavior, which has been previously observed for other pNIPAm based coatings Table . The stick angle has been shown to be close to the true equilibrium contact angle and as such the value of the stick angle can be used to estimate the average contact angle of the prepared films.…”
Section: Resultssupporting
confidence: 74%
“…This approach for thermoresponsive substrate preparation offers a convenient, simple, and cheap alternative for producing thermoresponsive surfaces to expensive and complex methods used elsewhere. The films were used for the passaging of hMSCs without the interference of animal derived trypsin . However, as the thickness of the cast films increased the surfaces became less bioadhesive and the numbers of cells which attached declined.…”
Section: Introductionmentioning
confidence: 99%
“…The fi lms were used for the passaging of hMSCs without the interference of animal derived trypsin. [2][3][4] However, as the thickness of the cast fi lms increased the surfaces became less bioadhesive and the numbers of cells which attached declined.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it is found that PNIPAM hydrogel can induce skeletal muscle inflammation response [58]. Furthermore, the in vitro test has proved that NIPAM-based thermoresponsive substrates didn't activate macrophages [59]. Accordingly, it is less probable that PNIPAM induces inflammation response, and the in vivo inflammation response might be induced by the mechanical damage when a certain volume of PNIPAM-gel was injected into tissues.…”
Section: For Tunel Analysis Apoptosis Was Only Obvious In Mptp+salinmentioning
confidence: 98%